Mobile Money and Financial Inclusion: Evidence from Lesotho - Thatho, Teboho (Faculty of Commerce, 2021)
This study seeks to examine the relationship between mobile money and financial inclusion in Lesotho in order to assess the viability of mobile money as a tool for advancing Lesotho's financial inclusion agenda. The study uses a number of deposit bank accounts as a proxy for financial inclusion (FI) and a dependent variable in three vector autoregression (VAR) bivariate models. Each of the three mobile money variables; number of mobile money registered accounts (MMC), number of agents (MMA) and volumes of mobile money transactions (MMT) are regressed against financial inclusion to investigate the relationship with each. The results indicate that among the three proxies of mobile money, only two have a relationship with financial inclusion: MMC and MMT. MMA does not show any relationship with financial inclusion. The relationship between FI and MMT is one-way from FI to MMT, which is not important for the purpose of this study. The MMC relationship with FI is the opposite of that of MMT and FI. There is a positive causal relationship from MMC to FI, indicating the positive influence of mobile money accounts of financial inclusion. The paper recommends that the government of Lesotho creates an enabling regulatory environment that supports the adoption and growth of mobile money in order to improve financial inclusion.